2013
DOI: 10.3109/2000656x.2012.755988
|View full text |Cite
|
Sign up to set email alerts
|

Muscle fibre types of the lumbrical, interossei, flexor, and extensor muscles moving the index finger

Abstract: The aim of this study was to determine the fibre types of the muscles moving the index fingers in humans. Fifteen forearms of eight adult cadavers were used. The sampled muscles were the first lumbrical (LM), first volar interosseous (VI), first dorsal interosseus (DI), second flexor digitorum profundus (FDP), second flexor digitorum superficialis (FDS), and extensor digitorum (ED). Six micrometer thick sections were stained for fast muscle fibres. The procedure was performed by applying mouse monoclonal anti-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 5 publications
1
14
0
Order By: Relevance
“…2005; Hwang et al . 2013) may result in differences in EMG‐sampled fibre‐type and explain discrepancies between the muscle activation patterns of the thigh (Burnley, 2009) and the forearm (this study). Lastly, although this study did not characterize fibre type, variability among subjects in recruitment patterns and the significant association between changes in RMS and TF pot (Fig.…”
Section: Discussionmentioning
confidence: 72%
“…2005; Hwang et al . 2013) may result in differences in EMG‐sampled fibre‐type and explain discrepancies between the muscle activation patterns of the thigh (Burnley, 2009) and the forearm (this study). Lastly, although this study did not characterize fibre type, variability among subjects in recruitment patterns and the significant association between changes in RMS and TF pot (Fig.…”
Section: Discussionmentioning
confidence: 72%
“…In addition, the distal intrinsic muscles may require more corticospinal drive than more proximal muscles (Palmer and Ashby 1992; Turton and Lemon 1999), leaving them more vulnerable to reduced neural activation post-stroke. Furthermore, intrinsic muscles may suffer from disproportionately greater underactivation due to changes occurring within the muscles: intrinsic muscles are composed predominantly of Type II muscle fibers (Hwang et al 2013), which have been shown to be particularly prone to atrophy post stroke (Dattola et al 1993; Hu et al 2007). …”
Section: Discussionmentioning
confidence: 99%
“…Performances of high intensity exercise can activate anaerobic glycolytic pathways for up to three minutes [47], a length of time similar to task duration in this study. This dependence on anaerbiosis may have been facilitated by the relatively high proportion of type II fibres in the FDS (41%) [48], which is much higher that the 20% reported in the adductor pollicis [49]. The exercise protocols in previous reports likely had greater involvement of aerobic pathways based on the fiber type proportion of the adductor pollicis [49], work to rest ratios (5 s on, 5 s off), and longer task durations [8,9,18].…”
Section: Discussionmentioning
confidence: 87%